IMPLEMENTATION OF THE MULTIFACTOR EVALUATION PROCESS METHOD FOR THE ELIGIBILITY OF PROVIDING ADVANCED TEACHER PROFESSIONAL ALLOWANCES AT THE EDUCATION OFFICE OF ASAHAN REGENCY - Frans Andrean Hasibuan; William Ramdhan; Wan Mariatul Kifti (Informatika, Universitas Jenderal Soedirman, 2022)
The teacher certification program is a way to improve the quality of teachers so that the quality of education is increasing. Where the performance appraisal process for each certification teacher is carried out every six months, namely by providing a report that is assessed by the teacher certification/standardization worker team, where the teacher performance appraisal report is still carried out in file collection and archived so as to allow for inaccuracies in the data and values ​​given so that it This will affect the selection of teacher certification eligibility. The method used in this research is the MFEP method which is one of the methods of decision support systems. This method was chosen because it is more efficient than other methods included in the completion of Multi Attribute Decision Making (MADM). Utilization of MFEP requires a relatively shorter calculation time. Based on this, in selecting the feasibility of providing teacher professional allowances or teacher certification, it is necessary to build a decision support system design for the feasibility of providing advanced teacher professional allowances at the Asahan District Education Office. The results obtained are the highest preference score of 4,435 named Siti Khairani Butar-Butar and the results of the system implementation can help performance in the selection of certification teachers. So it can be concluded that this system can provide convenience in obtaining assessment results effectively on a decision support system for the feasibility of providing advanced teacher professional allowances at the Asahan District Education Office.